Ethical Challenges of Using bST and Transgenic Animal - Bhuiyan, ASM Anwarullah (Bangladesh Journal of Bioethics, 2013)
This article examines whether using Bovine Somatotrophin (bST) and Transgenic Animal is compatible with the norms of animal welfare, environment, and public health. We cannot oppose its usefulness all on a sudden. Despite the usefulness of animal biotechnology, we cannot ignore the different adverse effects of this technology. All of these bring forth different ethical challenges. What is the environmental impact of this technology? Another ethical challenge is related to animals welfare and humans health. In order to assessing the ethical challenges, this article has opted for Mephams ethical matrix, which is a practical approach for addressing broader policy issues. I have focused on the application of this ethical matrix upon some contexts of animal biotechnology, such as bST and transgenic animal. Through the analysis, this article came to the conclusion that there are no short curt ways to reach an agreement on the application of animal biotechnology. DOI: http://dx.doi.org/10.3329/bioethics.v4i3.17372 Bangladesh Journal of Bioethics 2013; 4(3):1-10